Stages from the contemporary Iraqi history (1963-1968) in the secret press; Tareek Alshaab as a modal - Qays, Saif Adnan Irhayyim (International Journal of Psychosocial Rehabilitation, 2020)
The sixties decade of the twentieth century is the most prominent decade in the political conflicts and coups led by the leaders of that institution belonging to the relevant political ideologies of a national dimension. Those political conflicts led by the military personnel’s affected the Iraqi political situation. The secret newspaper Tareek Alshaab is The mouthpiece of the secret Iraqi Communist Party. It represents the opposition, which is considered a negative stance. The significance of the present study stems from the fact that it deals with the political issues of that stage according to the Communist Party’s vision of the events in Iraq. That vision may coincide or contradict according to its reading of the political stage or its attempt to undermine the policy of the anti-Communist ruling regimes as a destructive principle. The secret newspaper Tareek Alshaab represents the only example in the Iraqi political scene after the closure and leaving of many of the Iraqi press in light of the policy of closure and follow-up by the successive Iraqi governments. Many may differ in trying to criticize the newspaper’s positions, as they are often contradictory to political reality or they are far from the real vision of the public events. But, it deals with these events as an opponent of the regime in many cases. This can be explained in the positions that are more strict in interpreting the political facts that always contradict the party's philosophy. Tareek Alshaab always explained the negative aspects of the events as being from the reality of the regimes that It is always called a military "dictatorship", which has become an attribute associated with the history of Iraq since the July 14, 1958 revolution, which was later followed by a long series of bloody coups because they began to abuse their political opponents who are against their approach. In turn, this goes beyond the style of peaceful opposition. Tareek Alshaab was considered a model for the Iraqi opposition press, which bears the slogan "correcting the situation" in light of the presence of the military at the head of the authority, described on its pages of conditions that are far from the spirit of civilization based on Bringing a constitutional and democratic life away from the individual spirit that has become an attribute inherent to the ruling regimes in Iraq since the fall of the monarchy until the period under discussion.